1958
DOI: 10.1084/jem.107.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Cholesterol Content of Serum and Tissues, and Atherogenesis in the Rat

Abstract: Hypertensive patients are subject to a greater degree of atherosclerosis than are comparable normotensive individuals (1). Studies by Moss, Kelly, Neville, Bourque, and Wakerlin in dogs (2) and by Bronte-Stewart and Heptinstall in rabbits (3) indicate that induced arterial hypertension intensifies the atherosclerosis produced by dietary methods.Most observers (1) attribute this correlation between hypertension and the severity of atherosclerosis to local damage to the vessels produced by the pressure or turbul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1960
1960
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Deming et al (22), in studying the effect of experimental hypertension on atherogenesis in the rat, concluded that among animals on an atherogenic diet there was a positive correlation between elevation in blood pressure and serum cholesterol concentration. In attempting to assess the role of salt as distinct from that of desoxycorticosterone they concluded that salt was without effect on plasma lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deming et al (22), in studying the effect of experimental hypertension on atherogenesis in the rat, concluded that among animals on an atherogenic diet there was a positive correlation between elevation in blood pressure and serum cholesterol concentration. In attempting to assess the role of salt as distinct from that of desoxycorticosterone they concluded that salt was without effect on plasma lipids.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, we are aware of no evidence which would suggest that salt plays a role in atherogenesis either in experimental animals or man. Indeed, in the experimental studies of atherosclerosis alluded to above (19,22,23) the authors noted specifically that the excess salt ingestion failed to increase the atherosclerotic lesions. Nonetheless, if excessive salt ingestion is capable of elevating plasma lipids it may conceivably affect atherogenesis as well.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that rats will develop atherosclerotic lesions when maintained on the latter diet (13), but in the present study, rats were sacrificed before they had developed gross atherosclerotic lesions in the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…(19). At that time, earlier studies by others in the chicken (42), rat (43), and rabbit (44) furnished no support for this hypothesis. Subsequently, however, it was reported (45) that the incidence of myocardial and renal infarcts as well as the deposition of fat in the aortas of rats on an atherogenic diet were increased when 1-2 % saline replaced tap water for drinking, without associated changes in blood pressure.…”
Section: Inmentioning
confidence: 89%